Exploring the relationship between narrative complexity and recovery from substance misuse. (4th May 2021) - Rowlands, David; Youngs, Donna; Canter, David
ABSTRACT: Background/Aims: Research highlights a relationship between cognitive complexity and coping capacity. Narrative studies with psychiatric patients show that development of more complex ideas about self, others, and situations facilitates positive responsiveness to psychosocial challenges. Extending this line of inquiry, the present study examines the relationship between cognitive complexity in narratives and recovery from substance misuse. Method: The 'Life as a Film' (LAAF) task was used to collect narratives from a sample of 32 active or recovering substance users. LAAF accounts were coded for number of 'characters, ' 'events, ' and 'ideas, ' which were summed to give narrative complexity (NC) scores. A recovery inventory (RI) was used to compare NC with recovery outcomes. Results: Data showed a significant correlation between NC and RI scores (r =.61, p < .01), illustrating a relationship between greater cognitive complexity and recovery. Outliers from the general trend were discussed with reference to different intervention experiences. Conclusions: Findings indicate that increased NC relates to substance misuse recovery. Measures of NC produced intriguing insights, notably a facility in the LAAF for studying reflective processing and cognitive differentiation. Observations inform subtler analysis in subsequent LAAF studies, examining 'idea content' and treatment effects.